Protective Effects of Dietary Supplements Containing Probiotics, Micronutrients, and Plant Extracts Against Lead Toxicity in Mice - Zhai, Qixiao; Yang, Liu; Zhao, Jianxin; Zhang, Hao; Tian, Fengwei; Chen, Wei (Frontiers in Microbiology, 2018)
Lead (Pb) intoxication is a serious food safety issue, and the development of relevant dietary strategies is an area of ongoing research. In this study, two different dietary supplements were designed and evaluated for their effects against Pb toxicity in mice. Dietary supplement A contained grape seed extract, tea polyphenols and Lactobacillus plantarum CCFM8661, and dietary supplement B contained vitamin C, calcium carbonate, zinc acetate and L. plantarum CCFM8661. The results showed that both dietary supplements could effectively decrease Pb levels, protect aminolevulinic acid dehydratase, superoxide dismutase and catalase activities and recover glutathione, zinc protoporphyrin and malondialdehyde levels in tissues and blood of mice. A step-through passive avoidance task confirmed that the dietary supplements could recover the learning and memory capacities of Pb-exposed mice. The protective effects of both dietary supplements to alleviate oxidative stress and cognitive impairments were superior to the chelator treatment. Administration of the dietary supplements during Pb exposure offered more significant protection than administration after Pb exposure. Animal safety evaluation also indicated that these dietary supplements barely induced side effects in the mice. This study provides evidence that dietary supplements containing probiotics, micronutrients and plant extracts can be considered a new dietary strategy against Pb toxicity.